Weekly earthquake prediction in a region of China based on an intensive precursor network AETA - Xie, Jinhan; Yong, Shanshan; Wang, Xin’an; Bao, Zhenyu; Liu, Yibin; Zhang, Xing; He, Chunjiu (Frontiers in Earth Science, 2022)
Once a majority of earthquakes occur without prediction, it is very likely to have a huge impact on human society. To solve the worldwide challenging problem of earthquake prediction, our laboratory has developed a set of sensory systems to monitor the abnormal activity of geological signals before an earthquake happened in China. At present, more than 300 stations have been deployed, and the observation time has exceeded 4 years. Based on the various geological activity collected, a local correlation tracking method is used to capture signal anomalies before an earthquake, and then the ROC curve is used for the evaluation of the predictive accuracy. The method is applied in the Sichuan-Yunnan area weekly, verifying the forecast within a 91-week time frame and a 30-week time frame. The method proposed in this paper has earthquake prediction ability with a rate of over 70%. It promotes and contributes to helping people avoid the fear of unpredictable earthquakes.